IN SILICO PRIMER DESIGN AND ANNEALING TEMPERATURE OPTIMIZATION TO AMPLIFY THE FRAGMENT OF gyrB GENE Mycobacterium tuberculosis ISOLATE P010 USING POLYMERASE CHAIN REACTION - Handayani, Putu Irma (Journal of Health Sciences and Medicine; Vol 2 No 1 (2018): JHSM (February 2018), 2018)
One of the factors causing XDR-TB is due to mutations in the Mycobacterium tuberculosis gene, one of them is in the gyrB gene. Amplification of gyrB gene fragments from Mycobacterium tuberculosis DNA using Polymerase Chain Reaction (PCR) method. The amplification process by the PCR method requires a pair of primers (forward and reverse) to limit the area to be amplified. The current study aims to obtain the best primer pair generated by in silico design using Clone Manager Suite 6 program while simultaneously optimizing the annealing temperature to amplify the fragment of gyrB Mycobacterium tuberculosis. The template used in designing the primer is the sequence of gyrB Mycobacterium tuberculosis H37Rv isolate obtained from NCBI database of genbank code AL123456.3. The current study obtained a pair of primer which respectively had 19 oligonucleotide length and the best annealing temperature of 56ºC. The primer is be able to do in silico amplification of the fragment of gyrB Mycobacterium tuberculosis gene isolate P010 in the nucleotide area range from 1271-1755 bp with 485 bp fragment length.